The British Periodical Press and the French Revolution 1789-99 - Andrews, S. author. aut Link
XI, 280 p.
Keywords: This study challenges the conventional polarities used to describe British politics of the 1790s; Pitt versus Fox, Burke versus Paine, Church versus Dissent, ruling class versus working class, Jacobin versus anti-Jacobin. Such polarities were sedulously promoted by Pitt's wartime government, which applied 'Jacobin' shamelessly to all its critics and opponents, and thus foreshadowed the McCarthyite tactic of guilt by association. The author seeks to make the less strident but more persuasive contemporary voices again audible. He takes seriously those who questioned the necessity for Burke's crusade to destroy the French republic, and who deplored Britain's alliance with the partitioners of Poland.